HUBUNGAN ANTARA NORMA HUKUM DENGAN ASAS HUKUM - Ari Rahmad, Dedy Triyanto; Wairocana, I Gusti Ngurah; Dyah Satyawati, Ni Gusti Ayu (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013, 2013)
A relationship between the principle of legal norm when viewed in passing the ruleof law on a legal system is the principle of legal norm as a fundamental norm that be abasic though in legal system that formulated to be the rule of legislation. In Article 5and Article 6 Act No.12 in 2011 of Regulations, the problem is the principle of legalnorm has been directly concerning the establishment rule of law. The formulation of theproblem that can be drawn is how the relationship between the principle of the rule oflaw with the law? This problem will be researched with the normative legal researchmethod to produce an argumentation based on the theory as prescript in finishing theproblem faced. Acording to the author, the principle of legal norm is used as a materialof the consideration by the legislature in the formation a rule of legislation. Therefore,the law makers should not make a principle of legal norm to be a rule of law in articlesof the law.
Keywords: Relationship, legal norm